Sistem Pakar Deteksi Keaslian Toner HN Dengan Menggunakan Metode Certainty Factor - Yani, Ika Fitri; Buulolo, Efori; Sianturi, Lince T; Suginam, Suginam (TIN: Terapan Informatika Nusantara, 2021)
An expert system is defined as a branch of artificial intelligence that uses special knowledge possessed by an expert to solve a particular problem quickly. This study aims to design an expert system to detect the authenticity of HN toner using the certainty factor method. So that with this system, women know the difference between genuine and unoriginal HN toners and how to deal with them before consulting or buying drugs to a beauty doctor.